Microwave Rapid Sintering of Al-Metal Matrix Composites: A Review on the Effect of Reinforcements, Microstructure and Mechanical Properties - Penchal Matli (18807523) (2016)
Aluminum metal matrix composites (AMMCs) are light-weight materials having wide-spread use in the automobile and aerospace industries due to their attractive physical and mechanical properties. The promising mechanical properties of AMMCs are ascribed to the size and distribution of the reinforcement, as well as to the grain size of the matrix. Microwave rapid sintering involves internal heating of aluminum compacts by passing microwave energy through them. The main features of the microwave sintering technique are a short processing time and a low energy consumption. The aim of this review article is to briefly present the microwave rapid sintering process and to summarize the recent published work on the sintering and properties of pure Al and Al-based matrix composites containing different reinforcements. Other Information Published in: Metals License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/met6070143